Forests and water in South America. Issue 5 (26th December 2016) - Jones, Julia; Almeida, Auro; Cisneros, Felipe; Iroumé, Andres; Jobbágy, Esteban; Lara, Antonio; Lima, Walter de Paula; Little, Christian; Llerena, Carlos; Silveira, Luis; Villegas, Juan Camilo
Abstract: South America is experiencing rapid change in forest cover, of both native and planted forest. Forest cover loss is primarily attributable to fire, logging, and conversion of native forest to agriculture, pasture, and forest plantations, and types of change vary within and among the many diverse types of forests in South America. Major changes in forest cover and growing policy concerns underscore an urgent need for research on sustainable forest management and water ecosystem services in South America. Differences in land ownership and management objectives create trade‐offs between wood production and water ecosystem services from forests. Work is needed to quantify how forest change and management affect ecosystem services, such as wood production versus water provision. Current scientific understanding of forest management effects on water ecosystem services in South America has important limitations, including a scarcity of long‐term records and few long‐term integrated watershed studies. Industry, government, universities, and local communities should collaborate on integrated applied studies of forests and water. Data archiving and publically available data are required. The creation of national networks and a multi‐country South America network to identify and implement common water research protocols, share results, and explore their implications would promote common and well‐supported policies. Hydrologists working in South America are well placed to tackle the challenges and opportunities for collaborative research that will maintain the intrinsic values and water ecosystem services provided by South America's forests.